2006
DOI: 10.1631/jzus.2006.b0981
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced free radicals and antioxidant defense systems in schizophrenia: A comparative study

Abstract: Abstract:Objective: To examine changes of blood oxidative-antiovidative level in schizophrenic patients and its relationship with clinical symptoms. Methods: Forty-six Chinese patients met DSM-IV (Diagnostic and Statistical Manual of Mental Disorders-IV) criteria for schizophrenia and fifty age-and sex-matched healthy controls were enrolled in the present study. Baseline psychiatric symptom severity was assessed with brief psychiatric rating scale, positive and negative syndrome scale on the blood draw day. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 32 publications
2
21
2
Order By: Relevance
“…34 The presence of SOD in various compartments of our body enables it to dismutate superoxide radicals immediately they are produce and protects the cells from oxidative damage. SOD activities observed in this study among the schizophrenic patients with positive, negative, and cognitive symptoms show no significant difference from the controls although SOD activity was marginal reduced; contrary to the studies conducted by researchers 12,13,15,30 in which they reported decreased SOD activity and other studies 35e37 reported increased SOD activity among schizophrenic patients compared to the control subject; there were a lot contradictions in the activity of SOD in schizophrenic patients. GSH-Px neutralizes hydrogen peroxide by taking hydrogen from two GSH molecules resulting in two H 2 O and one GSSG.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…34 The presence of SOD in various compartments of our body enables it to dismutate superoxide radicals immediately they are produce and protects the cells from oxidative damage. SOD activities observed in this study among the schizophrenic patients with positive, negative, and cognitive symptoms show no significant difference from the controls although SOD activity was marginal reduced; contrary to the studies conducted by researchers 12,13,15,30 in which they reported decreased SOD activity and other studies 35e37 reported increased SOD activity among schizophrenic patients compared to the control subject; there were a lot contradictions in the activity of SOD in schizophrenic patients. GSH-Px neutralizes hydrogen peroxide by taking hydrogen from two GSH molecules resulting in two H 2 O and one GSSG.…”
Section: Discussioncontrasting
confidence: 99%
“…The enzyme GSH-Px then regenerates GSH from GSSG with NADPH as a source of hydrogen. In the present study erythrocyte GSH concentration and the activity of GSH-Px were significantly reduced in shizophrenic subjects with the three major symptoms, this was in agreement with recent studies 12,13,15,30 in which they reported decreased activity of GSH-Px in schizophrenic patients; likewise, other researchers 35,38,39 reported reduction in concentration GSH in their studies. CAT activity is one of the most important mechanisms by which RBC dispose of H 2 O 2 produce by dismutation reaction of O 2 in a cell.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some studies have examined peripheral concentrations of the free radical nitric oxide (NO) in patients with schizophrenia by measuring its metabolites, nitrites and nitrates, but have yielded inconsistent results. Whilst some have found elevated plasma NO Li et al, 2006;Taneli et al, 2004 ;Yanik et al, 2003;Zoroglu et al, 2002) and reduced polymorphonucleocyte NO (Srivastava et al, 2001) in those with schizophrenia compared with controls, no significant changes were found in plasma and platelet NO (Srivastava et al, 2001). Comparatively lower concentrations of the NO metabolites were found in the cerebrospinal fluid (CSF) of schizophrenia patients (Ramirez et al, 2004) compared with control patients who presented with noninflammatory and non-degenerative neurological conditions, but these metabolites were significantly increased in a sample of post-mortem caudate specimens (Yao et al, 2004).…”
Section: Assays Of Oxidants and Antioxidantsmentioning
confidence: 97%
“…Significant GSH deficiency has subsequently been reported (Altuntas et al, 2000). Reduced levels of the major antioxidant enzymes, superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px), have also been found in patients with schizophrenia compared with controls (Ben Othmen et al, 2007;Li et al, 2006;Ranjekar et al, 2003). Others have reported unchanged levels for these three enzymes (Srivastava et al, 2001), or altered concentrations of individual enzymes (Abdalla et al, 1986;Akyol et al, 2002;Altuntas et al, 2000;DietrichMuszalska et al, 2005;Herken et al, 2001;Kuloglu et al, 2002c ;Zhang et al, 2006a).…”
Section: Assays Of Oxidants and Antioxidantsmentioning
confidence: 99%